Afferent loop obstruction with obstructive jaundice and ileus due to an enterolith after distal gastrectomy: A case report. (2018) - Sato, Koki; Banshodani, Masataka; Nishihara, Masahiro; Nambu, Junko; Kawaguchi, Yasuo; Shimamoto, Fumio; Sugino, Keizo; Ohdan, Hideki
Highlights: An enterolith occurring in the duodenal afferent loop after distal gastrectomy, leading to obstructive jaundice and ileus is rare. Although afferent loop enterolith formation is uncommon, it should be considered when a patient with a history of B-II gastrectomy or Roux-en-Y reconstruction presents with fever, abdominal pain, or other symptoms suggesting acute cholangitis. Surgical treatment should be considered for afferent loop obstruction or intestinal obstruction that is refractory to conservative treatment. Abstract: Introduction: Afferent loop obstruction is an uncommon complication associated with Billroth II reconstruction or Roux-en-Y reconstruction after gastrectomy. Moreover, cases where the obstruction is caused by enterolith are rare. Here, we report a rare case of afferent loop obstruction caused by an enterolith after Roux-en-Y reconstruction of gastrectomy; subsequently, leading to ileus in the ileum. Presentation of case: An 84-year-old man who received a Roux-en-Y distal gastrectomy for gastric cancer presented with symptoms of fever and jaundice 14 months later. Computed tomography (CT) scan revealed an enterolith in the duodenal afferent loop and a dilated intrahepatic bile duct. Although the obstructive jaundice and fever disappeared with conservative therapy, ileus occurred due to the movement of the enterolith into the ileum, which was refractory to conservative therapy. Therefore, enterotomy was performed to remove the enterolith, and the patient had an uneventful recovery. Histologically, the enterolith derived from food residue. No postsurgical sign of recurrence has been noted for 6 months. Conclusion: We report a rare case where an enterolith in a duodenal afferent loop after distal gastrectomy led to obstructive jaundice, and subsequently, caused ileus by its movement into the ileum.